Ecological restoration in high-altitude mining areas: evaluation soil reconstruction and vegetation recovery in the Jiangcang coal mining area on the Qinghai-Tibet Plateau - Feng, Shaohua; Li, Zhiwei; Zhang, Ce; Qi, Ran; Yang, Liya (Frontiers in Environmental Science, 2025)
IntroductionThis study evaluates the effectiveness of soil reconstruction and restoration in the Jiangcang coal mining area on the Qinghai-Tibet Plateau, where harsh environmental conditions pose significant challenges to ecological restoration.MethodsTwo phases of ecological restoration were implemented, with outcomes assessed based on vegetation coverage, species diversity, biomass, soil properties, and community similarity.ResultsThe results demonstrate that soil reconstruction significantly improved soil fertility, vegetation coverage, and community stability without noticeable degradation over time. The use of sheep manure increased species diversity by introducing native seeds, addressing the shortage of suitable grass species in alpine areas. Comparatively, the second phase of restoration, which included soil reconstruction, has elevated the vegetation coverage to 80%, matching natural background levels, and has also demonstrated superior outcomes in terms of soil stability, nutrient content, and other aspects compared to traditional methods. While aboveground biomass showed rapid recovery, belowground biomass lagged, indicating a need for longer-term restoration. Restored slopes exhibited higher similarity to natural alpine meadows compared to platforms, suggesting the dominance of the artificially seeded species on the platform areas hinders the reproduction of other species, which is unfavorable for the evolution of vegetation diversity.DiscussionThis study emphasizes the effectiveness of soil reconstruction, organic amendment, and other restoration measures, providing important experience and reference for mine ecological restoration in similar high-altitude mining areas.